Economic freedoom, income inequality and economic growth in developing countries - Ismail, Norhazlin (2014)
The importance of economic freedom and income inequality on economic growth has been extensively investigated. Income inequality itself is a problem that needs to be addressed. Yet, the dilemma whether economic freedom and income inequality actually help to explain the corresponding differences in across countries economic growth rates are still in debate. Thus, the aims of this study are to examine the link between income inequality and economic growth, to determine the effect of economic freedom on economic growth and to analyse the impact of economic freedom on income inequality. In thisstudy, two data sets are utilized corresponding to two economic freedom data sources. In the case where the economic freedom data set is obtained from Fraser Institute’seconomicfreedom 2012, thenumber of developing countries is 65 countriesover the period 1976-2010. In the case where the economic freedom data set is gathered from Heritage Foundation’s economic freedom 2012, the same sample countries are employed but the sample periods are from 1996-2010 since the first report started in 1995. Besides, the economic freedom, income inequality and economic growth data, data on institutions, investment, population, human capital and inflation are added in determining variation in economic growth. All the data are analysed using a dynamic system panel GMM estimation technique. Several important findings are drawn from the study. First, the finding indicates that income inequality has a negative effect on economic growth.Policy makers need to reduce income inequality either through government spending, human capital or through minimum wage policy. Second, economic freedom and institutions variables affect economic growth positively. The sub-indicators of Fraser Institute of economic freedom namely, legal system and property rights, freedom to trade internationally, sound money, and regulationarefound to have a positive effect on economic growth. The sub-indicators of Heritage Foundation of economic freedom namely,monetary freedom and trade freedom arefound to have a positive effect on economic growth whereasgovernment spending, property rights,and business freedom arefound to have a negative effect on economic growth. Since not all economic freedom sub-indicators contribute to the positive link, it is good for the policy makers to just concentrate on positive sub-indicators. Finally, this study found that economic freedom affects income inequality positively. An increase in economic freedom makes income inequalityworsen. Size of government, legal system and property rights, and freedom to trade internationally contribute to the positive relationship between economic freedom and income inequality. Hence, taking into consideration the influence of economic freedom on economic growth, and income inequality, policy makers need to just focus on sound money, and regulation. An increase in economic growth and income equality has been the centre of economic policymaking in many countries around the globe. As such, the issues presented in this study would serve as important guidelines to understand the influence of the economic variables on economic growth and income equality.